Simulation oftheactionpotential in the Hodgkin-Huxley model - Pušenjak, Rudolf; Oblak, Maks (Anali PAZU, 2022)
Cells are called excitable, when produce action potentials. Action potentials arise in neurons and muscle cells in the form of signals. Signaling mechanism causes the brain activity or muscular contraction.  Lipid layers of membrane cell act as a capacitor and variable membrane conductances are consequence of ion channels, which can open or close. On this basis, the cell membrane can be modelled as an electrical circuit. In the paper, equations of the Hodgkin-Huxley cell membrane model are derived by using fundamental electrical laws and first order kinetics. The gained mathematical model of the cell membrane is used in the simulation of the action potential by symbolic programming tool such as Mathematica®.
Keywords: Hodgkin-Huxley model; cell membrane; simulation of action potential